Penerapan Digital Wellness dalam Menggunakan Media Sosial untuk Mencegah Pelecehan Daring pada Generasi Z - Muhammad Rizky; Muzahid Akbar Hayat; Ade Nur Atika Sari (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to understand the implementation of digital wellness in social media usage as a preventive measure against online harassment among Generation Z. The research employs a qualitative approach with a phenomenological method to explore the in-depth experiences of five informants—active university students and social media users who have encountered online harassment. Data were collected through in-depth interviews and analyzed using the Colaizzi method to identify key themes. The results reveal five significant findings: social media usage patterns among Generation Z, their experiences with online harassment, the meaning of digital symbols in online interactions, the digital wellness strategies implemented, and how digital wellness is understood as a form of harassment prevention. These findings indicate that the experience of online harassment triggers awareness and preventive actions through digital wellness practices, including strategies such as digital detox, account selection, privacy settings, and the removal of specific applications. Theoretically, this study contributes to enriching the study of symbolic interactionism by linking the meaning of digital symbols to experiences of online harassment. Practically, it provides an overview of digital wellness strategies that Generation Z can implement to maintain a balance in social media use and prevent the recurrence of online harassment in the digital space.